Morphological Study on Age Related Changes in Cortical Thickness Across the Central Sulcus - Fatema, Kanij; Ara, Shamim; Afroz, Halima; Rahman, Mushfika; Sultana, Anjuman Ara (Anwer Khan Modern Medical College Journal, 2014)
The central sulcus, which is located between the primary motor and primary somatic sensory cortexes, is an important structure and landmark of the cerebral hemisphere. Localization of the central sulcus is essential before brain tumor resection. Difference of cortical thickness across the banks of the central sulcus is an important indicator for localizing the central sulcus. Cortical thickness varies with age and in many diseased conditions. This Cross-sectional analytical type of study is carried out to establish a normal standard in different age groups for Bangladeshi people in cortical thickness across the central sulcus. The present study was performed on postmortem cerebral hemispheres of 70 Bangladeshi people in different age groups. Total 140 cerebral hemispheres were taken from these cadavers. Among them lowest age was 22 years in both sexes and highest age was 58 years in male and 48 years in female. The samples were divided into four different age groups i.e. Group A (20-29 years), Group B (30-39 years), Group C (40-49 years) and Group D (50-59 years). All the samples were studied morphologically in the Department of Anatomy, Dhaka Medical College, Dhaka from January 2010 to December 2010. In the present study, thickness of cerebral cortex across the central sulcus decreased with advancing age. The thickness of anterior bank of central sulcus, thickness of posterior bank of central sulcus and cortical thickness ratio across the central sulcus were 2.64±0.15 to 3.41±0.38 mm, 1.67±0.10 to 2.12±0.22 mm and 1.57±0.03 to 1.62±0.04 respectively. The difference in mean thickness between anterior and posterior bank of central sulcus was statistically significant in all age group (p=0.001). The difference in mean thickness between left and right central sulci was not statistically significant in any age group. The difference in mean thickness of Anterior bank was statistically significant between group A and C (p<0.01), A and D (p<0.01), B and C (p<0.05), B and D (p<0.01) in both left and right central sulci. The difference in mean thickness of posterior bank was significant between group A and C (p<0.01), A and D (p<0.01), B and D (p<0.01) in both left and right central sulci. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18764 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 4-9